Hubungan Penggunaan Media Sosial Dengan Konsentrasi Belajar Pada Remaja SMP - Alifiani, Herna (UKInstitute, 2024)
Various groups have mastered the use of social media, if social media is not used wisely, it can reduce productivity and concentration when carrying out daily routines. Excessive use of social media for students can have an impact on the field of education which results in students becoming less enthusiastic about learning, but more often accessing things that are not related to learning and can imitate negative lifestyles that exist on social media, which can lead to learning achievement. decrease. Less than optimal learning concentration can affect unsatisfactory learning outcomes. The purpose of this study was to determine the relationship between the use of social media and the concentration of students studying at SMP Negeri 1 Ciruas in 2023. This research method is a quantitative method with a cross sectional approach. The sample in this study amounted to 110 respondents, the sample sorting technique was by means of data taken through the absence of each class and then the data on the names of the students were entered into the shuffle, the names that came out would be used as respondents. The measuring tool in this study was a questionnaire using a measurement scale in the form of a Likert scale. Data analysis in this study was univariate analysis and bivariate analysis using the SPSS program. The results of the Chi Square test obtained p = 0.008 so it can be concluded that there is a significant relationship between the use of social media and learning concentration. From the results of the analysis, the value of OR=3.651 was also obtained, meaning that students who use social media negatively will be 3.6 times at risk of experiencing poor concentration in learning. This research is expected to be a guideline or description for future researchers to be able to conduct research using other research methods, namely quantitative methods.